Extending the Legal Standing on Authority Disputes at the Indonesian Constitutional Court - Iswandi, Kelik (Constitutionale, 2023)
The growth of state auxiliary organs increases the possibility of conflicting authority. Regrettably, the Indonesian Constitutional Court can only settle authority disputes between constitutional state organs. It is based on Article 24C 1945 Constitution jo. Article 61 Constitutional Court Act 2003 jo. Article 2 Constitutional Court Regulation No. 08/PMK/2006. Thus, how does does authority dispute resolution involve state auxiliary organs? This subject is addressed by normative legal research, which examines secondary evidence in the form of laws, Constitutional Court decisions, and doctrines. Based on the statutatory and conceptual approaches, it is found that the rule of legal standing leads to multiple interpretations about which state organ can have a legal standing in the constitutional court. Furthermore, the legal standing requirements are quite narrow and need to be strengthened to respond to the constitutional dynamics in Indonesia, particularly with the emergence of state auxiliary organs. According to this study, state auxiliary organs, particularly those with constitutional importance, can fulfill legal standing standards. While for the authority dispute which involves other state auxiliary organs, it can be resolved based on their legitimacy. Therefore, Constitutional Court Regulation No. 08/PMK/2006 must be revised to accommodate the settlement of authority disputes between state auxiliary organs.